Trends in incidence of total or type 2 diabetes: systematic review. (11th September 2019) - Magliano, Dianna J; Islam, Rakibul M; Barr, Elizabeth L M; Gregg, Edward W; Pavkov, Meda E; Harding, Jessica L; Tabesh, Maryam; Koye, Digsu N; Shaw, Jonathan E
Abstract: Objective: To assess what proportions of studies reported increasing, stable, or declining trends in the incidence of diagnosed diabetes. Design: Systematic review of studies reporting trends of diabetes incidence in adults from 1980 to 2017 according to PRISMA guidelines. Data sources: Medline, Embase, CINAHL, and reference lists of relevant publications. Eligibility criteria: Studies of open population based cohorts, diabetes registries, and administrative and health insurance databases on secular trends in the incidence of total diabetes or type 2 diabetes in adults were included. Poisson regression was used to model data by age group and year. Results: Among the 22 833 screened abstracts, 47 studies were included, providing data on 121 separate sex specific or ethnicity specific populations; 42 (89%) of the included studies reported on diagnosed diabetes. In 1960-89, 36% (8/22) of the populations studied had increasing trends in incidence of diabetes, 55% (12/22) had stable trends, and 9% (2/22) had decreasing trends. In 1990-2005, diabetes incidence increased in 66% (33/50) of populations, was stable in 32% (16/50), and decreased in 2% (1/50). In 2006-14, increasing trends were reported in only 33% (11/33) of populations, whereas 30% (10/33) and 36% (12/33) had stable or declining incidence, respectively. Conclusions: The incidence of clinically diagnosed diabetes has continued to rise in only a minority of populations studied since 2006, with over a third of populations having a fall in incidence in this time period. Preventive strategies could have contributed to the fall in diabetes incidence in recent years. Data are limited in low and middle income countries, where trends in diabetes incidence could be different. Systematic review registration: Prospero CRD42018092287.